Investigation of graphene addition to a mixture of biodiesel and tire pyrolysis oil: impact on engine performance and emissions characteristics - Prabhu S, Sadashiva; Natesan, Kapilan; Shivaprakash, Y. M.; Mazlan, Norkhairunnisa; Gurumurthy, B. M. (Springer Nature, 2026)
In many countries, the disposal of waste tires poses a serious environmental threat, leading to air, soil, and water pollution. This problem can be effectively mitigated by converting waste tires into fuel through pyrolysis. In this study, two major innovations were introduced: the incorporation of tyre pyrolysis oil (TPO) as a blend to biodiesel to enhance its volatility and combustion characteristics, and the use of graphene nanoplatelets as an additive to further improve combustion efficiency and reduce exhaust emissions owing to their superior thermophysical properties. The engine tests conducted with a blend of 80% Karanja biodiesel and 20% TPO(B80T20) at constant speed and varying loads demonstrated that the combined addition of TPO and graphene significantly improved brake thermal efficiency and reduced harmful emissions. The optimum graphene concentration of 75 mg/L yielded a 6.2% increase in brake thermal efficiency, an 8.94% rise in exhaust gas temperature, an 18.75% reduction in CO, 25% reduction in HC, an 8.16% increase in nitrogen oxides, and a 10.16% decrease in smoke levels compared to B80T20 at full load. Furthermore, regression analysis was performed to correlate engine performance and emission characteristics, and a cost analysis with graphene addition was conducted to assess the economic viability of the proposed approach.